Comparative Proteomic Analysis of the Effect of the Four-Herb Chinese Medicine ANBP on Promoting Mouse Skin Wound Healing. (September 2017) - Chen, Li; Hou, Qian; Zhou, Zhong-Zhi; Li, Mei-Rong; Zhong, Ling-Zhi; Deng, Xiang-Dong; Zhu, Zi-Ying; Cheng, Zhong-Yi; Zhu, Jun; Xiang, Cong-Lian; He, Wen-Jun; Fu, Xiao-Bing
Traditional Chinese medicine has great potential to improve wound healing. ANBP, the mixture of 4 Chinese herbs— Agrimoniapilosa, Nelumbonucifera, Boswelliacarteri, and Pollen typhae —is effective in trauma treatment while its mechanism is still elusive. In this study, quantitative proteomics and bioinformatics analyses were performed to decipher the possible roles of ANBP in accelerated wound healing of mouse skin. Among all 3171 identified proteins, 90, 71, 80, and 140 proteins were found to be differently expressed in 6 hours, 3 days, 7 days, and 14 days ANBP-treated tissues compared with corresponding control tissues, respectively. The result showed that different biological processes and pathways were activated at different healing stages. At the early healing stage, ANBP treatment mainly affected several biological processes, including immune and defense response, vascular system restoration, hemostasis and coagulation regulation, lipid metabolism and signal transduction, while muscle tissue, hair, epidermis, extracellular matrix and tissue remodeling related activities were the major events in ANBP promoted later wound healing. This is the first quantitative proteome study of ANBP-treated wound tissues, which provide a new perspective for the mechanism of ANBP accelerated wound healing and is of guiding significance for clinical application of ANBP in trauma disorders cure.